2018
DOI: 10.1038/s41598-018-27113-w
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of long noncoding RNA and mRNA expression profile in children with obesity by microarray analysis

Abstract: Long noncoding RNAs (lncRNAs) have an important role in adipose tissue function and energy metabolism homeostasis, and abnormalities may lead to obesity. To investigate whether lncRNAs are involved in childhood obesity, we investigated the differential expression profile of lncRNAs in obese children compared with non-obese children. A total number of 1268 differentially expressed lncRNAs and 1085 differentially expressed mRNAs were identified. Gene Ontology (GO) and pathway analysis revealed that these lncRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 46 publications
3
40
0
1
Order By: Relevance
“…Supporting the present data, previous studies have reported the induction of several lncRNAs in adipose tissue and targeting the main transcription factors of lipogenesis and adipogenesis, including PPARγ and SREBP-1 [11,[37][38][39][40][41]. For instance, knockdown of RP11-20G13.3 significantly decreased expression of markers of adipocyte differentiation: PPARγ, C/EBPα, and adiponectin [14]. Moreover, correlation analysis demonstrated that lncRNA RP11-20G13.3 in adipose tissue from obese and non-obese children was positively associated with obesity indices, circulating levels of insulin, LDL-C,and hs-CRP [14].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Supporting the present data, previous studies have reported the induction of several lncRNAs in adipose tissue and targeting the main transcription factors of lipogenesis and adipogenesis, including PPARγ and SREBP-1 [11,[37][38][39][40][41]. For instance, knockdown of RP11-20G13.3 significantly decreased expression of markers of adipocyte differentiation: PPARγ, C/EBPα, and adiponectin [14]. Moreover, correlation analysis demonstrated that lncRNA RP11-20G13.3 in adipose tissue from obese and non-obese children was positively associated with obesity indices, circulating levels of insulin, LDL-C,and hs-CRP [14].…”
Section: Discussionsupporting
confidence: 88%
“…For instance, knockdown of RP11-20G13.3 significantly decreased expression of markers of adipocyte differentiation: PPARγ, C/EBPα, and adiponectin [14]. Moreover, correlation analysis demonstrated that lncRNA RP11-20G13.3 in adipose tissue from obese and non-obese children was positively associated with obesity indices, circulating levels of insulin, LDL-C,and hs-CRP [14].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Other lncRNAs, such as U90926, MIR221HG, and RP11-20G13. 3, have also been shown to be negatively related to adipogenesis (101)(102)(103). These studies indicate that lncRNAs regulate white adipogenesis through lncRNA-protein, lncRNA-mRNA, and lncRNA-miRNA interactions.…”
Section: Role Of Lncrnas In White Adipocyte Adipogenesismentioning
confidence: 79%